Sosialisasi Program Sawit Rakyat Dalam Rangka Peningkatan Ekonomi Rakyat Kabupaten Nagan Raya Provinsi Aceh - Aswin Nasution; Sri Handayani; Bagio Bagio; Agustiar Agustiar; Sufriadi Sufriadi (Medan Resource Center, 2022)
This article aims to discuss the socialization of the people's palm oil program in the context of improving the people's economy in Nagan Raya Regency, Aceh Province. The government's focus on the oil palm rejuvenation program is supported by a replanting subsidy policy that uses funds from the Oil Palm Plantation Management Agency (BPDPKS). The purpose of the socialization activity is to provide information about the oil palm rejuvenation program and to arouse community enthusiasm for oil palm cultivation in Nagan Raya Regency in order to improve the welfare of oil palm farmers. The socialization activity explained in detail and clearly how best to carry out oil palm rejuvenation, explained the advantages and disadvantages of oil palm rejuvenation techniques, as well as provided information about the requirements and stages of oil palm rejuvenation activities, and helped increase access to groups receiving funds from the Oil Palm Plantation Fund Management Agency (BPDPKS).